Challenges of integrated urban water and waste water management : Case Study of Romania - Amin Moradi; Ali Akbar Pourrahim; Amir Mahmoudzadeh (مهندسی و مدیریت ساخت)
Water pollution is a major global problem that requires continuous assessment and revision of water resources policy at all levels (from international waters to inland waters and wells). It has always been noted that water pollution is the cause of death worldwide. 99. 9% of pure water is converted after use into household sewage, and only 0. 1% of the share of this water make up other pollutants. Although this amount of pollutant is found at low concentrations, it can be dangerous, however, on a large scale (area, city). Human uses for living from various sources, which are obtained through the waste of their work. The use of water resources, depending on domestic, industrial and urban consumption, leads to the production of sewage. Integrated water resources management shows that there are many ways in which this sector is beneficial, including sewage management and the responsibility of its various departments: the country, local communities, users, operators and NGOs related to water resources. This article presents the regulations and the importance of integrated urban water management. The process followed in sewage management is trying to show a new way.